1989
DOI: 10.1007/bf02126603
|View full text |Cite
|
Sign up to set email alerts
|

Different pro-inflammatory profiles of interleukin 1 (IL 1) and tumor necrosis factor (TNF) in anin vivo model of inflammation

Abstract: The pro-inflammatory properties of IL 1 and TNF were investigated in an in vivo model of inflammation. IL 1 induced PMN leukocyte accumulation that was slow in onset, reaching a peak rate at 3-4 h and that was inhibitable by Actinomycin D and Cycloheximide. PMN leukocyte emigration was not associated with any significant plasma leakage. In contrast, TNF induced PMN leukocyte accumulation and oedema formation, that were rapid in onset and very short of duration (t1/2 6-10 min). TNF-induced plasma leakage was PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…47 Specifically, TNF␣-induced neutrophil accumulation was fast (maximum within 30 minutes), similar to responses induced by the chemoattractants fMLP or LTB 4 , and the response elicited by IL-1␤ was slow (maximum within 3 to 4 hours) and protein-synthesisdependent. 47,48 In summary, with the use of PECAM-1-deficient mice, the results of the present study clearly demonstrate a role for PECAM-1 as a regulatory molecule in leukocyte migration through vessel walls at sites of inflammation. However, our findings also highlight the fact that PECAM-1-independent leukocyte migration can occur in a temporal-and/or stimulusspecific manner.…”
Section: Discusssionsupporting
confidence: 62%
“…47 Specifically, TNF␣-induced neutrophil accumulation was fast (maximum within 30 minutes), similar to responses induced by the chemoattractants fMLP or LTB 4 , and the response elicited by IL-1␤ was slow (maximum within 3 to 4 hours) and protein-synthesisdependent. 47,48 In summary, with the use of PECAM-1-deficient mice, the results of the present study clearly demonstrate a role for PECAM-1 as a regulatory molecule in leukocyte migration through vessel walls at sites of inflammation. However, our findings also highlight the fact that PECAM-1-independent leukocyte migration can occur in a temporal-and/or stimulusspecific manner.…”
Section: Discusssionsupporting
confidence: 62%
“…The involvement of locally generated proteins in these responses was investigated by using the RNA synthesis inhibitor, actinomycin D. Co‐administration of actinomycin D with the cytokines markedly suppressed leukocyte adhesion (49%) and transmigration (67%) induced by IL‐1β, but had no effect on responses elicited by TNFα. The present observations are in agreement with the findings of Rampart and colleagues who reported that the accumulation of 111 In‐neutrophils in rabbit skin in response to IL‐1β, but not TNFα, was protein synthesis dependent (Rampart & Williams, 1988; Rampart et al ., 1989b). Interestingly, using a very similar model, Cybulsky et al .…”
Section: Discussionmentioning
confidence: 98%
“…The pro‐inflammatory cytokines, IL‐1β and TNFα, have many overlapping properties and as such are often used within experimental inflammatory models interchangeably. However, a number of studies have also demonstrated key differences in the mechanisms of action of these cytokines suggesting divergence in their molecular and cellular targets (Rampart et al ., 1989b; Nathan & Sporn, 1991; Thompson et al ., 2001). The aim of the present study was to further investigate differences in the mechanisms of action of these cytokines by specifically examining the contribution of protein synthesis and the endogenously generated phospholipid mediators, PAF and LTB 4 , in different stages of leukocyte migration elicited by IL‐1β and TNFα.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations